Extreme morphological diversity in a single species of Rhagada (Gastropoda: Camaenidae) in the Dampier Archipelago, Western Australia: review of the evidence, revised taxonomy and changed perspective. (6th September 2018) - Johnson, Michael S; Stankowski, Sean
Abstract: In the Dampier Archipelago, Western Australia, land snails of the genus Rhagada are exceptional in two respects: (1) they show greater morphological diversity over distances of less than 70 km than does the rest of the genus over distances of up to 2, 000 km; (2) the island morphospecies have complex, interspersed distributions, contrasting with the simple, broad-scale allopatric replacement of mainland species. Based largely on shell characteristics, this local diversity is currently recognized to encompass six species endemic to the Dampier Archipelago. We review here molecular and morphological evidence to show that almost all the diversity is attributable to a single, highly diverse species: the morphospecies are polyphyletic, are genetically very similar and do not form distinct genetic groups; furthermore, they are not morphologically distinct, but grade into one another. On this basis, we synonomize Rhagada dampierana Solem, 1997, R. intermedia Solem, 1997, R. minima Solem, 1997, R. perprima Iredale, 1939 and part of R. angulata Solem, 1997 (all from the Dampier Archipelago) and R. plicata Preston, 1914 (from Barrow Island and the Montebello and Lacepede Islands) under the earliest available name, R. elachystoma (Martens, 1877). Morphological variation in this inclusive R. elachystoma exceeds that in the rest of the genus. From this new perspective we discuss the origins and maintenance of extreme morphological diversity within a single species in the Dampier Archipelago.